Immediate Healing for Personality Development: An Approach towards Yoga Concept and Spiritual Effect - Eltonsi, Hadi (Highlights on Medicine and Medical Science Vol. 1, 2021)
Statement of the Problem: Clients receiving psychotherapy require several sessions even if with drugs and use of will power over time. Purpose of the Treatment: Achieving immediate non medicinal effortless painless healing without complications. For personality development, relief of neurotic disease, psychosomatic symptoms and diseases, treating emotional obesity and smoking. Method: After joint analysis with Client and definition of psychological and physical goals of treatment, the healer as a trained behavioral, cognitive and logo psychotherapist arrives with client to a new corrected understanding of the case and roots of conflicts in childhood, taking around 2 hours, then in less than an hour performs non verbal interpersonal hypnosis with transfer of energy and telepathy to client till deep sleep when he implants the required personality, ideas, emotions, motives and attitudes into the subconscious embodying the required state. The subconscious and conscious mind will have same agreed upon analysis and targets for immediate results in that session of 3 hours. Results: The healer got patent in Egypt 2016 for his discovery of The Immediate Healing for Personality Development and for mentioned purposes. Up till now treating more than 700 cases aging between 12 and 80 years with relief of more than 80% of cases either totally or mostly. Conclusion: Immediate non medicinal revolutionary life transforming healing for a wide spectrum of cases achieving higher grades of maturity, insight, harmony and efficiency saving client time, effort, interests and complications. Also used to maturate community leaders to be a trouble shooter model efficient leaders with team spirit.